Efficacy of single dose praziquantel against Schistosoma mansoni in East Africa: a systematic review and meta-analysis - Miseganaw Sisay; Tadesse Hailu; Destaw Damtie; Kindu Geta; Lamesgen Zelalem; Degisew Misganaw (Scientific Reports)
Abstract The genus Schistosoma causes a schistosomiasis which is one of the neglected tropical diseases that pose a major threat to public health in East Africa. Praziquantel (PZQ) is the first line drug to treat human schistosomiasis. However, there is scarcity of pooled and summarized data on PZQ efficacy to policymakers. Articles were searched from PubMed, Google Scholar, Web of Science, and Scopus databases. In total, 87 published articles were retrieved. Only studies conducted in English that reported the efficacy of PZQ against Schistosoma mansoni, regardless of the year, and studies with more than fifty positive cases were included in the present study. Excel software was used to extract the name of the authors, the total sample size, number of cured participants, the study area, and the year of publication. The pooled efficacy of PZQ against S. mansoni was analyzed using CMA Version 2.2 software. A total of 21 studies fulfilled the inclusion criteria for the present systematic review and meta-analysis. The overall pooled efficacy of PZQ was 85.0% (95% CI: 80.0-89.0%) against S. mansoni. In subgroup analysis, the efficacy of PZQ against S. mansoni was 90.4% in Ethiopia, 71.2% in Kenya, 97.9% in Rwanda, 75.4% in Tanzania, and 68.4% in Uganda. Its heterogeneity was high (I2 = 94.8), and the there is no publication bias between studies. The overall effectiveness of PZQ against S. mansoni in East Africa is doubtful. Therefore, repeated doses should be advocated.